Pengaruh Substitusi Tepung Pisang Terhadap Mutu Kue Kering - Sifia Silfia (Institution for Industrial Research and Standardization of Industry - Padang, 2012)
Banana (Musa paradisiaca) is a highly nutritious fruit that is a source of vitamins, minerals and carbohydrates. Bananas are used as table fruit, smoked bananas, mashed bananas and banana flour. The purpose of this research was to extend the shelf life of banana which was processed into cookies. The research was conducted by treatment of comparison between banana flour and wheat flour, which is 100:0%, 80:20%, 60:40%, 40:60%, and 0:100%. The product was then analyzed the moisture content, ash, protein, and organoleptic test for taste, aroma, texture, and storage resistance. The results showed that comparison treatment of banana flour and wheat flour 80:20%, providing optimal results with 3.55% moisture content, 1.19% ash content, 14.25% protein, texture, flavor and aroma, and preferably keep hold more than 16 weeks.ABSTRAKPisang (Musa paradisiaca) adalah buah yang sangat bergizi yang merupakan sumber vitamin, mineral dan juga karbohidrat. Pisang dijadikan buah meja, sale pisang, pure pisang dan tepung pisang. Tujuan penelitian ini adalah untuk memperpanjang masa simpan pisang yang diolah menjadi kue kering. Penelitian dilakukan dengan perlakuan perbandingan tepung pisang dengan tepung terigu, yaitu 100:0%, 80:20%, 60:40%, 40:60% dan 0:100%. Produk kemudian dianalisis kadar air, abu, protein, dan uji organoleptik terhadap rasa, aroma, tekstur, dan ketahanan simpan. Hasil penelitian menunjukkan bahwa perlakuan tepung pisang dengan tepung terigu 80:20% memberikan hasil optimal dengan kadar air 3,55%, kadar abu 1,19%, protein 14,25%, tekstur, rasa dan aroma disukai serta ketahanan simpan lebih dari 16 minggu.